Synthesis and Evaluation of (1,4-Disubstituted)-1,2,3-triazoles as Estrogen Receptor Beta Agonists - Edward A. Wetzel; Grace C. Corriero; Sandra Brown-Ford; Daniel S. Sem; William A. Donaldson (MDPI AG, 2022)
Estrogen receptors (ER) are nuclear hormone receptors which are responsible for sex hormone signaling in women. A series of (1,4-disubstituted)-1,2,3-triazoles 5-21 were prepared by reaction of azidophenols with terminal alkynes under Fokin reaction conditions. The products were purified by column chromatography or recrystallization and characterized by NMR and HRMS. The compounds were tested for binding to ERβ via a ligand displacement assay, and 1-(4-hydroxyphenyl)-α-phenyl-1,2,3-triazole-4-ethanol (21) was found to be the most potent analog (EC50 = 1.59 μM). Molecular docking of 5-21 within the ligand binding pocket of ERβ (pdb 2jj3) was performed and the docking scores exhibited a general qualitative trend consistent with the measured EC50 values.